Formulation and Pharmacokinetic Evaluation of Microcapsules Containing Pravastatin Sodium Using Rats - Venkatesh Dinnekere Puttegowda; Roopa Karki; Divakar Goli; Sajal kumar Jha; Manjunatha Panduranga Mudagal (Scientifica)
Pravastatin Sodium has a cholesterol lowering agent. It has shorter half-life and undergoes first-pass metabolism. Frequent dose is required in case of conventional dosage form. The purpose of the study is to formulate and evaluate microcapsules containing Pravastatin Sodium by complex with cholestyramine resins coated with Eudragit RLPO and Eudragit RSPO polymers for achieving control release. Complexation of drug on resin was carried out by batch method. Microencapsulation was carried out by nonaqueous solvent evaporation method. Pharmacokinetic studies were done by using rats. The intermediate stability studies were carried out on the most satisfactory formulations. FTIR, X-ray diffraction, and DSC spectra of drug, drug-resinates, and polymers revealed no chemical interaction. The % DEE and % yield were observed for formulations of f1 to f7 that were varied from 97.1 ± 0.8 to 98.9 ± 0.5% and 95.0 ± 3.25 to 98.8 ± 7.1%, respectively. Most satisfactory formulation, f6, showed drug release up to 72.6%. No changes in % DEE and % CDR were observed after stability studies. Microcapsules of f6 formulation achieved best performance regarding in vitro drug release and from pharmacokinetic evaluation mean residence time was found to be 6.3 h, thus indicated, Pravastatin Sodium microcapsules were released and absorbed slowly over a prolonged period of time.